Level of Knowledge of the Tamalanrea District Community Tamalanrea Jaya District in Makassar City About Use of Antibiotics - Murniati, Murniati; Bulu, Katarina (Politeknik Sandi Karsa, 2022)
Antibiotics are drugs used to treat infectious diseases. The high incidence of infectious diseases results in the high use of antibiotics. The use of antibiotics is necessary if the cause of the disease has been ascertained by bacteria. Inappropriate use of antibiotics will lead to antibiotic resistance. The purpose of this study was to determine the level of knowledge of the community in Tamalanrea District, Tamalanrea Jaya Village in Makassar City about the use of antibiotics. The method used in this research is descriptive, namely research that includes surveys with data collection techniques in the form of questionnaires. This research was carried out on Jalan Bung RT 004/RW 001 and the time of the research was carried out in June by distributing questionnaires to 50 respondents or the community according to the criteria. The results of this study indicate that the level of knowledge of the community in Tamalanrea District, Tamalanrea Jaya Village in Makassar City about the use of antibiotics, the percentage of knowledge obtained is 84.7% so that it is included in the category of high knowledge level.